Evaluasi Sistem Pengelolaan Dana Bergulir di Kantor Seketariat Badan Kerjasama Antar Gampong (BKAG) dan Unit Pengelolaan Kegiatan (UPK) Kecamatan Ranto Peureulak - Yusriani; Jamil, Muhammad (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2022)
Revolving funds are a form of government intervention in the economic field in order to improve justice. One of the characteristics of revolving funds is that these funds are channeled to the community/community groups, charged back with or without added value, and re-rolled back to the community/community groups or known as revolving funds. The purpose of the Management of Activities of Revolving Fund Management System Office of the Secretariat of the Inter- gambling Cooperation Agency (BKAG) and the Unit (UPK) of Ranto Peureulak District The research method is a qualitative approach. This qualitative approach is used in order to obtain descriptive data in the form of written words from people or samples used as respondents. the results of practical work that have been described in previous chapters, the authors can draw a conclusion from the Evaluation of the Revolving fund management system at the secretariat office of the Inter-gambling Cooperation Agency (BKAG) and the Activity Management Unit (UPK) of Ranto Peureulak District, which is very useful for the sub-district community Ranto Peurelak.